Emerging adaptivity in probability learning: How young minds and the environment interact - Thoma, Anna I; Newell, Ben R; Schulze, Christin (Journal of experimental psychology. General, 2025)
Children often have to choose between two or more probabilistically rewarded options. How early in life do they learn to choose adaptively? Connecting research on ecologically rational probability matching in adulthood with research on the benefits of cognitive immaturity in childhood, we compared children's (3-11 years; = 362) and adults' ( = 121) repeated choice behavior in a child-friendly probability learning task. We implemented two static and one ecologically plausible statistical environment as between-subjects conditions. Behavioral and computational modeling analyses provided converging evidence for perseveration tendencies in 3- to 4-year-olds and adaptive choice diversification from age 6 years onward. On average, school-aged children showed a stronger tendency for exploration, whereas adults were better able to overcome this tendency in favor of exploitation. Our findings emphasize the importance of implementing ecologically plausible task environments in research on cognitive development and contribute a novel repeated choice perspective to the discussion on the adaptive functions of wide exploration in childhood. (PsycInfo Database Record (c) 2025 APA, all rights reserved).